Essentials of language testing for Malaysian teachers - Abd. Samad, Arshad (Universiti Putra Malaysia Press, 2019)
The second edition of Essentials of Language Testing for Malaysian Teachers, acknowledges the many of developments that have taken place in Malaysia. At the same time, it maintains the approach of first discussing traditional concepts and ideas related to language testing and evaluation followed by an exploration into more recent notions about test¬ing, drawing attention to the qualitative and social as well as the psychometric aspects of tests and assessments. Each chapter presents a brief discussion of important concepts as well as terminology and issues related to the focus of the chapter. Examples of tests and assessment are also provided and discussed whenever relevant. This book is intended as a bridge between the more traditional concepts of testing and measurement in teaching English as a Second Language to one that is more contemporary and compatible with modern views of language learning and education. It hopes to address important and relevant issues that can help the reader better understand the demands and challenges of testing and evaluation in TESL especially in Malaysia. While the book is intended as a resource in understanding language testing and assessment for the undergraduate testing course in the TESL programme at Universiti Putra Malaysia, it is also relevant to the needs of language teachers in Malaysian schools.